Peningkatan Keterampilan Menulis Puisi Siswa berdasarkan Pengalaman Pribadi dengan Teknik Pancingan Kata Kunci pada Siswa Kelas VII UPT SMP Negeri 3 Alla Kabupaten Enrekang - Suwarti Suwarti (CV. Syntax Corporation Indonesia, 2022)
Writing is one of the language skills. Writing skills are basically the skills to express thoughts and feelings through written language. Based on initial observations, poetry writing skills about the personal experiences of seventh grade students of UPT SMP Negeri 3 Alla, Enrekang Regency are still low. This study aims to describe the increase in the ability to write poetry about personal experiences with keyword provocation techniques and describe changes in student behavior after participating in learning. This research was conducted in 2 stages, namely the first cycle stage and the second cycle stage, while the data collection used test and non-test techniques, non-test techniques included observations, journals, and interviews. Data analysis used quantitative and qualitative approaches. Based on data analysis in the first cycle the average score was 67.38 with sufficient category, in the second cycle there was an increase of 8.67% with an average class score of 76.05 included in the good category, the increase in the average class score was followed by an increase in the average score of each aspect of the assessment. In the aspect of conformity of the content to the theme, the average in the first cycle was 78.57 with a good category, and increased in the second cycle of 84.29 with a good category, in the diction aspect, the average in the first cycle was 66.67 with enough category, and in the second cycle there was an increase of 79.05 in the good category, in the rhyme aspect, the average in the first cycle was 60.48 with the sufficient category, and in the second cycle there was an increase of 70.48 in the good category. typographical aspect, the average in the first cycle was 58.57 which was included in the less category, and in the second cycle there was an increase of 64.76 which was included in the sufficient category.